Guidelines for Enhancing the Administration of Learning Management Through Digital Technology Platforms in Schools Under Surin Primary Educational Service Area Office 3 - Deeying, Malinee; Sitthisua, Thanyatep; Sonjai, Songdej (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study the current status, desired status, and necessity of the development guidelines for learning management administration using digital platform technology of educational institutions and 2) to study the guidelines and evaluate the development guidelines for learning management administration using digital platform technology of educational institutions under the Office of the Primary Educational Service Area 3, Surin. The research was conducted according to the mixed-method research design. The population consisted of 292 school administrators and teachers in the academic year 2024. The sample group in this research consisted of 146 school administrators and 146 teachers, totaling 292 people. The research instruments were questionnaires with a reliability of 0.88 for the entire questionnaire. There were 9 purposive experts in the focus group discussion process and 7 experts in the evaluation of the appropriateness and feasibility of the guidelines. Data analysis included mean, standard deviation, need index, and content analysis. The research results found that: 1. The current level of development of administration in learning management using digital platform technology of educational institutions under the Office of the Primary Educational Service Area 3, Surin, is at a moderate level. The desired condition of development of administration in learning management using digital platform technology of educational institutions is at the highest level overall in all aspects. The necessity of development of administration in learning management using digital platform technology of educational institutions, ranked from most to least important, is as follows: 1) Development of personnel skills and abilities 2) Digital learning media 3) Teaching and learning management and learner development 4) Planning and policy determination and 5) Evaluation and quality development, respectively. 2. Guidelines for development of administration in learning management using digital platform technology of educational institutions under the Office of the Primary Educational Service Area 3, obtained from group discussions, totaled 10 guidelines, as follows: 1) Administrators must determine policies that promote the development of systematic learning management via digital platforms. with a plan to develop information technology infrastructure 2) Executives must have a plan to mobilize resources to support the development of digital platform technology. 3) Executives should encourage personnel to continuously participate in training and development through the PLC process and create a learning network through the digital technology learning center. 4. Executives should encourage teachers to develop research skills, to be able to apply research results and disseminate them to the academic community. 5) Executives should encourage teachers to use digital platform technology in teaching and learning and to develop students to be able to learn anywhere, anytime. 6) Executives must create an environment conducive to teaching and learning through digital platform technology. 7) Executives must promote the establishment of an online database system for teachers to develop digital learning media. 8) Executives should organize training on digital learning media development for teachers by creating a memorandum of understanding (MOU) with an agency with expertise in digital learning media development. 9) Executives conduct a quality assurance system audit through digital platform technology using their own user accounts. 10) Executives should promote an evaluation system to develop quality in management through digital platform technology. The evaluation approach is most appropriate and highly feasible.